Ocimum Sanctum: Phytochemistry, Therapeutic Uses Pharmacological Activities and Its Anticancer Activities - Santosh Kumar S.R.; Manoj Manjunath Bongale; Prakash Pralhad Sarwade; K.Vijayalakshmi; Mamta Goswami; Rapborlang Khongshei; Kavita Narayan Gaisamudre(Sarwade) (Asian Journal of Pharmaceutical Research and Development, 2025)
The practice of Ayurveda, which is based on the principles of living a healthy lifestyle and eating adaptogenic herbs on a regular basis, has the potential to alleviate a significant number of the chronic diseases that are the main cause of mortality across the globe. Tulasi, also known as Ocimum sanctum Linn, is considered to be the most significant herb in Ayurvedic medicine. Recent scientific research has demonstrated that it imparts a number of positive health effects. An increasing body of research indicates that the unique combination of pharmacological properties that tulsi possesses has the potential to alleviate stress on various levels, including the physical, physiological, metabolic, and psychological levels. Tulsi has been found to protect internal organs and tissues from the damaging effects of heavy metals and industrial pollutants, as well as against the impacts of physical stresses such as cold, excessive loudness, ischemia, and prolonged durations of physical exercise. This has been demonstrated through research. Plants that have medicinal properties are utilized on a daily basis by traditional healers in order to treat a wide variety of ailments. Ocimum sanctum Linn, a small herb that is widely distributed across India and is referred to as Tulsi in Hindi, has a long history of application in traditional medicine for the treatment of a wide range of ailments. These ailments include bronchitis, bronchial asthma, malaria, diarrhea, dysentery, skin diseases, arthritis, painful eye diseases, chronic fever, insect bites, and many others. There is some evidence to suggest that O. sanctum L. may possess qualities that include antibacterial, anticancer, antidiabetic, neuroprotective, and hepatoprotective. It has been demonstrated that O. sanctum L. possesses therapeutic value, as demonstrated by the pharmacological research that was incorporated into this study.